Are Immigrants and Girls Graded Worse? Results of a Matching Approach - David Kiss (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2011)
Using PIRLS 2001 and PISA 2003 data for Germany, this paper examines whether secondgeneration immigrants and girls are graded worse in math than comparable natives and boys, respectively. Once all grading-relevant characteristics, namely math skills and oral participation, are accounted for, pupils should obtain same school grades. Results of a matching approach and class fixed effects regressions suggest that second-generation immigrants have grade disadvantages in primary education which could bias their secondary school track choice. Regarding secondary school, most immigrants are not affected by grade discrimination and girls enrolled in upper-secondary school are systematically graded better.
Keywords: C40; I21; J15; 330; grade discrimination in primary and secondary education; school careers of immigrants and girls; matching frameworks; Migranten; Kinder; Frauenbildung; Bildungsniveau; Allgemeinbildende Schule; Bewertung; Deutschland